2020
DOI: 10.1108/dpm-01-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge adoption in post-disaster housing self-recovery

Abstract: PurposeThe purpose of this study is to explore communication of hazard-resistant construction techniques after disaster in the absence of outside influence. It further aims to unpack the barriers and drivers in the adoption of knowledge processes to identify strategic recommendations to enlarge adoption of safer construction practices by local construction actors. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…A larger proportion of environmental crisis studies (n = 14) reported on active KE [55,[67][68][69]71,73,74,76,77,79,81,84,85,109]. Theoretical frameworks underpinning active KE in environmental settings were aligned with participatory and collaborative principles, aiming to develop a more holistic understanding of a crisis inclusive of a range of knowledge [67][68][69]71,74,77,81,83]. Active KE environmental crisis approaches encompassed the exchange of formalised knowledge (e.g.…”
Section: Environmental Crisesmentioning
confidence: 99%
See 2 more Smart Citations
“…A larger proportion of environmental crisis studies (n = 14) reported on active KE [55,[67][68][69]71,73,74,76,77,79,81,84,85,109]. Theoretical frameworks underpinning active KE in environmental settings were aligned with participatory and collaborative principles, aiming to develop a more holistic understanding of a crisis inclusive of a range of knowledge [67][68][69]71,74,77,81,83]. Active KE environmental crisis approaches encompassed the exchange of formalised knowledge (e.g.…”
Section: Environmental Crisesmentioning
confidence: 99%
“…good practice recommendations, technical guidance), [75,78,83,85,86] organisational and policy/professional knowledge from different sectors and disciplines (e.g. water managers, NGOs and international agencies), [67,69,71,73,74,77,[81][82][83][84][85] PLOS ONE the knowledge of volunteers following a crisis such as information about the location of damage or weather conditions [71,76] as well as local contextual knowledge of communities living in affected areas [73,74,77,79,[81][82][83][84][85]. The use of scientific data/research and academic knowledge was referenced explicitly in a small number of studies [67,69,81,83,85].…”
Section: Environmental Crisesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study predicted the relief material demand and supply using a big datadriven dynamic estimation model. Hendriks and Opdyke (2020) focused on the views of stakeholders. They conducted an analysis of stakeholders' perspectives during the reconstruction phase in the aftermath of Typhoon Haiyan.…”
Section: Supply Chain Supply Network and Sustainability In The Humanitarian Aid Contextmentioning
confidence: 99%
“…However, it is unclear how the earthquake resistance of reconstructed housing differs for different intensities of humanitarian technical assistance (United Nations Human Settlements Programme (UN-Habitat) and AXA, 2019). In addition, little empirical research examines how communities self-recover after a disaster, when they are left to reconstruct with little to no technical assistance, using their own resources and knowledge (Hendriks and Opdyke, 2020;Maynard et al, 2017;Twigg et al, 2017). Furthermore, humanitarian assistance only reaches a small percentage of disaster-affected populations (Morel and Global Shelter Cluster, 2018).…”
Section: Introductionmentioning
confidence: 99%